1979
DOI: 10.1016/0304-3959(79)90077-0
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of headache in an urban and a rural population in northern Finland

Abstract: SYNOPSISInformation on the prevalence of headache and its characteristic features and the factor provoking it was collected using a questionnaire similar to that introduced by Waters. The questionnaire was posted to every inhabitant over 15 years of age in a defined urban and a defined rural area in northern Finland. The reliability of the questionnaire was tested by neurological examination of a random sample of 200 persons. The response rate was 74.0% in the urban and 79.5% in the rural area, a total of 3067… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
4

Year Published

1981
1981
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 7 publications
4
38
4
Order By: Relevance
“…In contrast to previous studies [14,[24][25][26][27], the present study found a strong association between cigarette smoking and headaches, headaches accompanied by migraine symptoms, and diagnosed The present study found no association between reported exercise and headaches or symptoms, while the Denmark study found a significant association between reported lack of physical activity and tension headaches [14]. That study [14] also found an association between tension and migraine headaches and sleeping problems, but not length of sleep.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous studies [14,[24][25][26][27], the present study found a strong association between cigarette smoking and headaches, headaches accompanied by migraine symptoms, and diagnosed The present study found no association between reported exercise and headaches or symptoms, while the Denmark study found a significant association between reported lack of physical activity and tension headaches [14]. That study [14] also found an association between tension and migraine headaches and sleeping problems, but not length of sleep.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are consistent with a cross-sectional study of headaches from Denmark [14] and other countries [24][25][26][27], in that no association was found with alcohol consumption. In contrast to previous studies [14,[24][25][26][27], the present study found a strong association between cigarette smoking and headaches, headaches accompanied by migraine symptoms, and diagnosed The present study found no association between reported exercise and headaches or symptoms, while the Denmark study found a significant association between reported lack of physical activity and tension headaches [14].…”
Section: Discussionsupporting
confidence: 91%
“…On the one hand, we lack knowledge about the kind of headaches that the men suffered from and it is therefore difficult to determine whether general prevalence is of any importance to our findings. On the other hand, abuse may have been a stressful experience and stress is a known headache trigger in both men and women (43)(44)(45). Interestingly, our findings are contrary to studies showing no relation between violence and headaches (17,18).…”
Section: Physical Health Lifestyles and Violencecontrasting
confidence: 57%
“…Collaboration between clinicians and epidemiologists in the conduct of community surveys of headache has been requested (6,8), since most earlier information from this field has been based on highly selected patient populations. The 1974 Pontypridd Headache Survey by Waters (8) is one of the few population based surveys.…”
mentioning
confidence: 99%